PENGARUH POLA OPERASI LOAD LIMIT DAN FREE GOVERNOR TERHADAP KINERJA TURBIN GAS PLTGU MUARAKARANG - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
Of electricity demand is very high, so as to reduce the impact of interference on the network system, the power plants are required to operate Free governor mode. But the pattern of the operation has external and internal impact plants. External impacts PLN P3B generation transmission system will be more stable. Disturbances in the system will be normalized by power plants operating in Free governor mode. Ie internal impact plant operation pattern Free governor mode will cause the load pattern to follow PLN P3B. Expenses continue to change may affect the efficiency and life of plant equipment. The performance of gas turbines at the plant commonly called the heat rate. The higher the heat rate indicates that the efficiency of the turbines is lower. The results of the analysis of the performance of gas turbines 2.2 with patterns limit load operation mode and free mode governor Muara Karang Blok 2 concluded that the pattern of the governor PLTGU free operation causes the fuel gas consumption increases so that the efficiency of gas turbines declined. In this study, the test results after maintenance heat rate (Turbine Inspection) is used as the value of the performance comparison of the performance of gas turbine during operation with a load limit and free patterns governor.